Use of bones taken from the operated areas of impacted third molars as autografts for implant placement: cases report - Antonius SS. Putra; Robby Ramadhonie; Poerwati S. Rahajoe (DiscoverSys Inc., 2018)
Objective: This report aims to explain how the bones taken from the operated areas of impacted third molars are used as autografts for implant placement.Methods: Two patients with missing maxillary incisor, lack of alveolar bone support, and impacted third molar underwent an implant placement procedure with bone grafting and third molar removal, subsequently. In both cases, the implant was placed and resulted in a dehiscence-typed defect. The defect was filled with an autograft harvested from the operated area of impacted third molar, and then covered with PRF membrane and titanium mesh. The wound was sutured accordingly and evaluation was taken 3 months following the procedure.Results: Under direct observation, in both cases, new bone formation appeared in the buccal region of the implant to the margin of the implant crestal. The implant was stable and no complications occurred.Conclusion: On the basis of this finding, it can be concluded that operated area of impacted third molar can be considered as an ideal alternative for donor sites for patients who needed bone grafts and third molar extraction simultaneously.